Breaking Out of Isolation : Becoming a Connected School Leader. - Cook, Spike C. (Corwin connected educators series., 2015)
Fresh ideas to help you meet the challenges of innovative leadership! Overcome the hurdles of being a school leader and stay ahead with this helpful guide to battling isolation and getting connected. Through powerful vignettes and strategies, you'll discover how innovation-minded school leaders connect to avoid isolation, lower stress, find support, and share ideas. Grow your professional practice and learn to: Jumpstart and sustain your Professional Learning Network Strategically and meaningfully connect with colleagues and staff Overcome isolation for lasting impact Includes tips for Twitter.